2015
DOI: 10.1038/tpj.2015.63
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphisms of ABCC5 and NOS3 genes influence doxorubicin cardiotoxicity in survivors of childhood acute lymphoblastic leukemia

Abstract: Anthracyclines are efficient chemotherapy agents. However, their use is limited by anthracycline-induced cardiotoxicity (CT). We investigated the influence of polymorphisms in doxorubicin metabolic and functional pathways on late-onset CT as estimated by echocardiography in 251 childhood acute lymphoblastic leukemia (cALL) patients. Association analyses revealed a modulating effect of two variants: A-1629 T in ABCC5, an ATP-binding cassette transporter, and G894T in the NOS3 endothelial nitric oxide synthase g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 45 publications
0
69
0
2
Order By: Relevance
“…When we limited the results to publications consistent with the revised label for Cardioxane, 13 clinical trials [6][7][8][9][10][11][12][13][14][15][16][17][18] and four meta-analyses or systematic reviews remained [19][20][21][22]. These meta-analyses and systematic…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When we limited the results to publications consistent with the revised label for Cardioxane, 13 clinical trials [6][7][8][9][10][11][12][13][14][15][16][17][18] and four meta-analyses or systematic reviews remained [19][20][21][22]. These meta-analyses and systematic…”
Section: Resultsmentioning
confidence: 99%
“…Dexrazoxane is an effective cardioprotectant in children Since the CHMP review, 11 relevant publications have examined the use of dexrazoxane in children [6,7,[9][10][11][12][14][15][16][17][18]. The Children's Oncology Group (COG) P9404 randomized trial evaluated oncologic efficacy, cardioprotective effectiveness and safety following dexrazoxane therapy in 537 children and adolescents with newly diagnosed T-cell acute lymphoblastic leukemia (ALL) or lymphoblastic non-Hodgkin lymphoma (Table 1) [6].…”
Section: Resultsmentioning
confidence: 99%
“…The solute carrier family (SLC) is responsible for anthracycline transport into the cell, while ABC (ATP-binding cassette) transporters are involved in energy-dependent anthracycline efflux from the cell. Significant associations have been found between ACT and SNPs in various SLC and ABC genes [33,[43][44][45].…”
Section: Cardiotoxicitymentioning
confidence: 97%
“…Mutant haplotypes of this gene have been associated with increased cardiac iron load, elevated troponin levels, and decreased LV fractional shortening [48,49]. Genes more directly involved in mitigating oxidative stress and subsequent tissue remodeling such as endothelial nitric oxide synthase 3 (NOS3) and hyaluronan synthase 3 (HAS3), have also been found to modify the risk of anthracycline dose-dependent cardiomyopathy risk [33,89].…”
Section: Cardiotoxicitymentioning
confidence: 98%
“…Reichwagen et al found that NADPH oxidase gene polymorphisms were associated with anthracyclineinduced cardiotoxicity in patients affected with B-cell lymphoma [75] . Krajinovic et al revealed that ABCC5 and NOS3 gene polymorphisms have been associated with the development of doxorubicin-induced cardiotoxicity in children with acute lymphoblastic leukemia [76] .…”
Section: Doxorubicin-induced Cardiotoxicity Correlation With Apoptosimentioning
confidence: 99%